Shaping service ecosystems: exploring the dark side of agency - Cristina Mele; Suvi Nenonen; Jaqueline Pels; Kaj Storbacka; Angeline Nariswari; Valtteri Kaartemo (Emerald, 2022)
Purpose
The extant service ecosystem literature rarely addresses the dark side of actors’ agency, which hinders further development of the service-dominant (S-D) logic, particularly with regard to understanding service ecosystem dynamics. Therefore, the purpose of this paper is to delineate the dark-side facets of actors’ agency that adversely affect actor-to-actor relationships and resource integration, in the context of shaping service ecosystems.
Design/methodology/approach
With abductive reasoning, this study seeks to reorient results from prior literature in accordance with empirical findings. The empirical data pertain to 21 firms in Finland, New Zealand, Singapore and Sweden, representing various industries, sizes, international reach, technologies, ownership forms and histories.
Findings
The dark side of agency emerges as an actor’s deliberate attempts to influence a service ecosystem to achieve self-interested benefits, despite understanding that these actions inhibit other actors from providing service and can be detrimental to other actors and the ecosystem. The findings also reveal three facets of the dark side: conflict, ambiguity and opportunism. The process of shaping service ecosystems is prone to systematic conflict, ambiguous and opportunistic behaviours occurring between the focal actors’ ecosystem and other ecosystems vying for the same set of resources.
Research limitations/implications
This study advances the S-D logic by addressing the crucial role of agency in a dialectical relationship with institutions and structures. Service-for-service exchanges can take place in asymmetric, ambiguous, opportunistic situations driven by self-interested motives.
Practical implications
Processes aimed at shaping service ecosystems can demonstrate the dark sides of actors’ agency, related to conflict, ambiguity or opportunism. Managers interested in shaping strategies should be prepared for this outcome.
Social implications
A service ecosystem perspective requires policy makers and regulators to reconsider their role in shaping processes. No “invisible hand” guides markets to equilibrium, so they should be more proactive in shaping ecosystems, rather than merely fixing market failures.
Originality/value
This research offers the first S-D logic-based investigation into the dark side of actors’ agency in shaping service ecosystems.